Management and employee buy-outs from the Australian public sector - Wieser, Oliver; Robbie, Ken; Wright, Mike (1997)
This paper seeks to extend our understanding of the nature and effects of privatization to the case of Austria, a relatively small economy in which management buy-outs have been a numerically important but neglected part of the privatization programme. The study reviews the development of privatization in Austria and sets management and employee buy-outs within this context. The paper identifies 35 privatization buy-outs, analysing their form and industrial distribution. Evidence from detailed interviews with the 22 largest is used to analyse the effects of buy-out on corporate change, the role of insiders and performance. Comparisons are made with the UK, where management and employee buy-outs have also been an important part of the privatization programme. - Reproduced
Keywords: Privatization - Australia; Public sector - Australia; Privatization